Simplified approach for fracture integrity assessment of bimetallic girth weld joint - BONORA, Nicola; RUGGIERO, Andrew; IANNITTI, Gianluca; Carlucci, A. (Volume 2B: Structures, Safety and Reliability, 2013)
Recent extensive use of Corrosion Resistance Alloy (CRA) as internal protection layer of standard carbon-steel pipes (clad and lined pipe) in the oil and gas industry requires an intensive use of bimetallic welds. Since some degree of defects in welds is inevitable, and in codes and standards (such as BS7910) the case of bi-metallic joint is usually not considered, some R&D's activities are ongoing to define specific design guidance for an Engineering Critical Assessment (ECA) aimed at determining flaw acceptance criteria for fabrication of bimetallic joints. Based on the limited guidance in the literature, proposed procedures for ECA on CRA welds seem not cover the root/hot pass weld region, for which the requirement of "zero defect" became mandatory. As direct consequence, it penalizes the weld fabrication rate, particularly if "J-lay" or "S-Lay" methods are adopted. Furthermore, they are investigating on cases where weld material is overmatching the base metal or for a limited partial overmatching, despite for CRA welds, such conditions, seem quite difficult to be fully met, if current consumable materials present in the marked are selected. Aim of present paper is to describe how any standard ECA procedure (ordinarily used to assess carbon-steel welds) may be alternatively adopted to assess CRA welds for clad & lined pipe material, if specific conditions are respected. For this purpose a few number of elastic-plastic Finite Element Analysis (FEA) is required to identify and/or extends the validity limits which have to be met in order to be conservative in the use of selected standard procedure. Outer, inner and under clad flaws, located along the weld fusion line, were investigated. Such approach, certainly leads to a quite conservatism, but gives the advantage to provide a safe flaws acceptance criterion in root/hot pass weld, and it may be also applied for any level of weld partial overmatching condition. Despite proposed simplified approach is suitable until moderate plastic straining, it may be ...